Telepathy, Mediumship and Psychology: Psychical Research at the International Congresses of Psychology, 1889–1905 - Alvarado, Carlos S. (Journal of Scientific Exploration, 2017)
The development of psychology includes the rejection of concepts and movements some groups consider undesirable, such as psychical research. One such example was the way psychologists dealt with phenomena such as telepathy and mediumship in the first five international congresses of psychology held between 1889 and 1905. This included papers about telepathy and mediumship by individuals such as Gabriel Delanne, Léon Denis, Théodore Flournoy, Paul Joire, Léon Marillier, Frederic W. H. Myers, Julian Ochorowicz, Charles Richet, Eleanor M. Sidgwick, and Henry Sidgwick. These topics were eventually rejected from the congresses, and provide us with an example of the boundary-work psychologists were engaging during the period to build their discipline. The height of such presentations took place at the 1900 congress, after which there was a marked decline in discussion on the topic that mirrored the rejection science at large showed for psychical research during the period in question.